Unexpected [videorecording (DVD)] - Vaccaro, Rodney; Camp, Anna, 1982-; Mazzello, Joseph, 1983-; Flynn, Neil, 1960-; Shane, Ryann; Grier, Nash, 1997-; Tarte, Bob (Breaking Glass Pictures, 2023)
Bob and Amy are at a crossroads: she wants to adopt a baby, but he doesn't. Will renovating a house and rescuing animals solve their problems? Will their new handyman and his son's pregnant girlfriend be the miracle they are looking for? A comedy about life, love, adulting, and a bunny named Binky.